ANALISIS MANAJEMEN SUMBER DAYA MANUSIA TERHADAP KINERJA KARYAWAN PADA CV. RIGEN TIMUR RAYA KOTA MAKASSAR - Sudirman Sudirman; Hamri Hamri; Suwardy Suwardy; Ihwal Asrul; Melisa Yanuar Susilo (Universitas Ichsan Sidenreng Rappang, 2025)
This research analyzes human resource management (HRM) strategies and practices and their impact on employee performance at CV. Rigen Timur Raya, an electrical telecommunication company. The study's background stems from indications of low productivity, high turnover, and low employee job satisfaction due to suboptimal HRM. Using a descriptive qualitative approach, data was collected through interviews, observations, and documentation, then analyzed thematically and via SWOT. Findings reveal that the company's HRM practices are informal: recruitment is based on acquaintances, training is unstructured, compensation lacks transparency, and performance appraisals are subjective. These factors lead to low motivation and job satisfaction, despite a family-like atmosphere being a strength. It is recommended that CV. Rigen Timur Raya improve its recruitment and selection systems, strengthen training and development programs, create a fair and transparent compensation system, and enhance performance appraisals and career paths. These improvements are expected to sustainably boost employee performance and satisfaction.